Kontribusi Umer Chapra Dalam Membangun Sistem Ekonomi Islam - Aji Damanuri (Justicia Islamica, 2004)
This study aims to analyze Umer Chapra's contribution to building an Islamic economic system and its relevance to the development of contemporary Islamic economics. The method used is qualitative research with a descriptive-analytical approach through a literature study of Chapra's works and the Islamic economic concepts he developed. The results show that Chapra emphasizes the integration of sharia principles and modern economic theory to create an equitable economic system. He criticized the weaknesses of the capitalist and socialist systems and offered an Islamic economic concept based on the maqāṣid al-sharī'ah, which prioritizes social welfare, fair distribution of wealth, and economic stability. His ideas became the basis for the development of Islamic economic policies in various countries. This study confirms that Chapra's theory has strong relevance in building a more inclusive and sustainable economic system.